The barrio gangs of San Antonio, 1915-2015 - Tapia, Mike (TCU Press, 2017)
Is there such a thing as a criminal class? -- San Antonio barrio group origins: micro-locality and community -- The paradoxes of barrio gang networks -- Social spheres and the 1950s barrio subculture -- The barrio landscape expands: the 1960s and 1970s -- The 1980s: prison gangs in Ol' San Antone -- Modern Chicano street gangs: 1990s-2015 -- Lessons from analyzing Chicano gang formations over time